Parental physical activity, parental mental health, children’s physical activity, and children’s mental health - Davidson, Gavin; Bunting, Lisa; McCartan, Claire; Grant, Anne; McBride, Orla; Mulholland, Ciaran; Nolan, Emma; Schubotz, Dirk; Cameron, Julie; Shevlin, Mark (Frontiers in Psychiatry, 2024)
Introduction -The benefits of physical activity for mental health and wellbeing, and the associations between parental mental health and children's mental health have been well established. These important issues tend to be examined separately however, and there is limited research on the associations between parent and child physical activity and mental health when all considered together. While family focused practice is recommended to provide support for parents who have mental health problems and their families, and includes various components (such as psychoeducation, support for mental health and parenting), promoting physical activity for parents and children is not usually a core component of these interventions. Methods -The Northern Ireland Youth Wellbeing Survey (NIYWS) aimed to provide estimates of the prevalence of mental health problems among children and young people. The survey also included questions about parental physical activity, parental mental health, and children's physical activity (for those aged 11-19). The main aim of the analysis reported in this article was to explore possible bivariate associations between parent and child physical activity and mental health, and also explore these associations when all considered together. Participants were included in the analysis where there were completed interviews for the young person and one of their parents, and both young person and parent provided responses in relation to questions on weekly physical activity (n = 882). Results -The findings highlight the positive associations between parental physical activity and parental mental health, and between children's physical activity and children's mental health. They also explore some of the more complex interactions between these four variables which suggest that gender may also be an important consideration. There were significant associations between father's physical activity and son's mental health; and son's physical activity and father's mental health. Discussion -These findings suggest that including support for parental physical activity and children's physical activity should be a routine component of family focused mental health interventions. It is important to acknowledge that there may be additional barriers to engaging in physical activity for families where a parent is experiencing mental health problems and these should also be explored and addressed.